A clinical study of urinary tract infections in diabetics and non-diabetics patients - Vinod, C. Sayee Sankar; Nareddy, Vishnu Anjan; Nagabhushana, M. V. (International Journal of Advances in Medicine, 2019)
Background: The main aim of the present study is to investigate the differences in clinical, microbiological, characteristics of Urinary tract infection between diabetic and non-diabetic patients and influence of diabetes on the spectrum of URO pathogens and the antimicrobial resistance in patients with urinary tract infections. Methods: The present study is conducted from February 2018-April 2019 in Narayana general hospital. A total of 181 diabetics and 124 non-diabetics are included. A thorough history examination investigations done. The final data was analysed using statistical package SPSS. The percentages in different categories were compared using chi square test and means were compared using student ‘t’ test. Results: The mean age among diabetic and non-diabetic patients was 60.2+/-13.79 years and 53.47+/-18.56 years. Fever is the most common presenting symptom. BPH was the most common predisposing factor in both diabetes and non-diabetes followed by indwelling catherization but there was no statistically significant difference. Diabetics with UTI majority (87.14%) had glyco HBA1C >6.5% with p<0.001. The prevalence of recurrent UTI is higher in diabetics compared to non-diabetics however difference was not statistically significant. Recurrent UTI is higher in females in both diabetics and non-diabetics. The presence of E coli is significantly higher in diabetics compared to non- diabetics. The antimicrobial resistance pattern was similar in both diabetic and no-diabetic subjects in E coli with maximum sensitivity to meropenem and least to ampicillin and there is no statistically significant difference. Conclusion: The host factors found to be associated with UTI are female sex, presence of diabetes, poor glycemic control, presence of fever. No correlation was noted with age, duration of diabetes and type of treatment for diabetes. An elevated HBA1C correlates with occurrence of UTI. Escherichia coli (E. coli) was the most frequent uropathogen. The resistance of uropathogens to antibiotics are similar in patients with and without diabetes and non-diabetes.